2001
DOI: 10.1046/j.1537-2995.2001.41121475.x
|View full text |Cite
|
Sign up to set email alerts
|

A study of 178 consecutive vasovagal syncopal reactions from the perspective of safety

Abstract: Syncopal reactions most commonly occur at the refreshment table, where preventive safety measures against trauma could be applied. A significant number of syncopal reactions occur offsite, where the environment is less safe. The injuries that occur, particularly to the head, may in rare cases lead to long-term sequelae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 21 publications
1
50
1
Order By: Relevance
“…In 2001, Newman et al also found a high number (46%) of subjects with tonic and myoclonic or twitching muscle activity after vasovagal responses during blood donation [22]. Though the number of blood donations increases until 50 years of age, the number of syncopal reaction rates was highest in patients under 40 years of age [22].…”
Section: Discussionmentioning
confidence: 98%
“…In 2001, Newman et al also found a high number (46%) of subjects with tonic and myoclonic or twitching muscle activity after vasovagal responses during blood donation [22]. Though the number of blood donations increases until 50 years of age, the number of syncopal reaction rates was highest in patients under 40 years of age [22].…”
Section: Discussionmentioning
confidence: 98%
“…Pre-syncope reactions (no loss of consciousness) and syncope reactions (loss of consciousness) decreased blood donor return rates by 29-37% and 58-78%, respectively, in comparison to donors who did not have a vasovagal reaction [15,37,38,40]. Syncope occurs in approximately 4-5% of vasovagal reactions [1] and in 0.12-0.27% [1,21,42] of allogeneic whole blood donations. 60-73% of the syncope reactions occur after the donor leaves the bed due to gravity, and 10-12% of the reactions occur after the donor leaves the blood collection site [41,42].…”
Section: Effects Of Vasovagal Reactions On Blood Donorsmentioning
confidence: 99%
“…Syncope occurs in approximately 4-5% of vasovagal reactions [1] and in 0.12-0.27% [1,21,42] of allogeneic whole blood donations. 60-73% of the syncope reactions occur after the donor leaves the bed due to gravity, and 10-12% of the reactions occur after the donor leaves the blood collection site [41,42]. Studies show that women, and especially smaller women, are more susceptible to gravity-precipitated syncope, and almost all syncope reactions that occurred after leaving the blood collection site occurred in women [41].…”
Section: Effects Of Vasovagal Reactions On Blood Donorsmentioning
confidence: 99%
“…Overall 26% and 22.5% of the males and female participants respectively had knowledge about blood donation however 21% and 16.8% of these and as a result some had also suffered trauma [13].…”
Section: Resultsmentioning
confidence: 98%